2018
DOI: 10.3390/app8122375
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Pressure Sensitivity of Carbon Nanofiber-Reinforced Polyurethane Cement

Abstract: The sensitivity of carbon nanofiber polyurethane cement (CNFPUC) was evaluated to determine whether the cement can act as an intelligent reinforcement material. The percolation thresholds at different polymer-to-cement ratios were determined through experimentation. Taking a specific carbon nanofiber (CNF) content of the percolation zone, several CNFPUC mixtures with different poly-ash ratios and silica fume contents were made. They were then sampled from the mixture and poured into a hexahedron CNFPUC test bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It has been well established that increasing CNF content leads to a decrease in the bulk resistivity of CNF-filled materials, with the highest drop within the percolation threshold concentration range [16,25]. More precisely, the bulk resistivity decreases most significantly in the concentration range at which nanofibers start forming a connected network.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that increasing CNF content leads to a decrease in the bulk resistivity of CNF-filled materials, with the highest drop within the percolation threshold concentration range [16,25]. More precisely, the bulk resistivity decreases most significantly in the concentration range at which nanofibers start forming a connected network.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the components can be found in Table 6. According to the existing experimental results, the content of CNF was in the seepage zone, and the CNFPUC had good sensitivity characteristics [23]. To test the bond performance between CNFPUC and concrete, the concrete was cut into 100 mm × 100 mm × 100 mm cubes by a concrete cutting machine.…”
Section: Preparation Of Cnfpuc Specimenmentioning
confidence: 99%
“…When the strain was close to the limit, the microcracks developed into main cracks, and the CNF fibers had few lap connections, thus the resistivity rose sharply until fracture. Through the change of resistivity in the bending process of CNFPUC, the three failure processes of elastic deformation, stable crack propagation, and unstable propagation were reflected [23].…”
Section: Mechanism Analysismentioning
confidence: 99%
“…The construction of environmentally friendliness materials with reinforced properties is also very important for environmental science. Yang et al [10] reported in this issue the industrial synthesis of self-sensing, self-monitoring intelligent carbon nanofibers (CNFs)-reinforced polyurethane cement (CNFPUC) materials. The using of CNFs for the fabrication of CNFPUC materials improved the varistor characteristics of materials, making CNFPUC as smart materials.…”
Section: New Materials For Environmental Sciencementioning
confidence: 99%
“…Based on their previous study on the synthesis of CNFPUC materials [10], Yang and Sun contribute another paper on the self-monitoring of bending fatigue cumulative damage of CNFPUC [13], in which detailed characterizations on the resistivity of CNFPUC by adjusting bending strain, stress level, cycle times, and temperate were performed. In addition, the relationship between the fatigue cumulative damage and the change of the resistivity of materials was further analyzed.…”
Section: New Techniques For Environmental Sciencementioning
confidence: 99%